The fortune - Shire, David 1937- (Powerhouse Films, 2024)
"Zwei Freunde haben eines Tages genug vom aufdringlichen Getue der Millionärstochter, mit der sie eine Hochzeitsreise zu dritt antreten mußten, und beschließen, die dümmliche Person zu beseitigen. "[...]Groteske mit nostalgischem Einschlag, die mit ihrer komischen Schlagseite an Slapstick-Komödien der 20er Jahre anknüpft [...]." [filmdienst.de]
Original: USA 1975
Indicator Blu-ray edition special features: High Definition remaster ; original mono audio ; audio commentary with critic and film historian Nick Pinkerton (2017) ; Mike Nichols and Elaine May in conversation (2006, 69 mins): the two friends and collaborators discuss many aspects of filmmaking after a screening of May’s Ishtar at New York’s Walter Reade Theater ; Professor Kyle Stevens on ‘The fortune’ (2017, 6 mins): appreciation by the author of Mike Nichols: Sex, language, and the reinvention of psychological realism ; isolated music and effects track ; image gallery: on-set and promotional photography ; new and improved English subtitles for the deaf and hard of hearing
Bildformat 2.39:1
Keywords: Film; Blu-Ray-Disc